Perlindungan Hukum Terhadap Karya Tulis Non-Ilmiah Yang Dimuat Dalam Media Sosial - Madia, Putu Bella Mania; Parwata, A.A Gede Oka (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022), 2022)
This study aims to examine the legal protection arrangements for non-scientific papers published on social media and legal sanctions related to plagiarism of non-scientific papers published on social media. This study uses a type of normative legal research method. The approach in this research is the statutory approach and conceptual approach. The legal materials in writing this research are obtained through literature study. The results of the study explain that legal protection for non-scientific written works published on social media is in accordance with the principle of copyright law protection, wich is based on the recognition of economic rights and moral rights, but these works have not received comperhensive protection because the copyright has not been registered. Legal sanctions related to plagiarism of non-scientific papers published on social media are in the form of imprisonment or a fine as stated in Article 44 Paragraph (1) letter a, Article 113 Paragraphy (2), and Article 120 of the Copyright Law, and in Article 380 Paragraph (1) of the Criminal Code. Settlement of copyright disputes can be reached through litigation or non-litigation.